Standard mandibular canine index of the Malaysian Indian student used for sex prediction in forensic dentistry - Ren, Beh Wee; Ardan, Rachman; Rikmasari, Rasmi (Padjadjaran Journal of Dentistry, 2010)
Identification of the unknown body is a medical, legal and humane responsibility of the forensic team to evaluate data relevant to the identification. The purpose of this research was to obtain necessary data to compute and analyze the Mandibular Canine Index (MCI) between Malaysian Indian males and females studying in Universitas Padjadjaran as well as to determine the Standard Mandibular Canine Index (Standard MCI) for the Malaysian Indian community. This research used a descriptive and analytical survey approach and was done though a stratified random proportional sampling technique. The result of this research established a statistical significant difference between males and females Mandibular Canine Index (MCI) with the level of confidence of 95% with the mean of males as 0.260Â±0.019 and females as 0.236Â±0.012. The Standard Mandibular Canine Index of the Malaysian Indian community was 0.248. The overall success to predict the sex using this Standard Mandibular Canine Index was 76.67%. It was concluded that Standard Mandibular Canine Index could be used for sex prediction as a supporting technique.